Thrombomodulin: a multifunctional receptor modulating the endothelial quiescence - Giri, Hemant; Biswas, Indranil; Rezaie, Alireza R. (Journal of thrombosis and haemostasis, 2024)
Thrombomodulin (TM) is a type 1 receptor best known for its function as an anticoagulant cofactor for thrombin activation of protein C on the surface of vascular endothelial cells. In addition to its anticoagulant cofactor function, TM also regulates fibrinolysis, complement, and inflammatory pathways. TM is a multidomain receptor protein with a lectin-like domain at its N-terminus that has been shown to exhibit direct anti-inflammatory functions. This domain is followed by 6 epidermal growth factor-like domains that support the interaction of TM with thrombin. The interaction inhibits the procoagulant function of thrombin and enables the protease to regulate the anticoagulant and fibrinolytic pathways by activating protein C and thrombin-activatable fibrinolysis inhibitor. TM has a Thr/Ser-rich region immediately above the membrane surface that harbors chondroitin sulfate glycosaminoglycans, and this region is followed by a single-spanning transmembrane and a C-terminal cytoplasmic domain. The structure and physiological function of the extracellular domains of TM have been extensively studied, and numerous excellent review articles have been published. However, the physiological function of the cytoplasmic domain of TM has remained poorly understood. Recent data from our laboratory suggest that intracellular signaling by the cytoplasmic domain of TM plays key roles in maintaining quiescence by modulating phosphatase and tensin homolog signaling in endothelial cells. This article briefly reviews the structure and function of extracellular domains of TM and focuses on the mechanism and possible physiological importance of the cytoplasmic domain of TM in modulating phosphatase and tensin homolog signaling in endothelial cells.